(untitled) (Gestão & Regionalidade, 2023)
This research addresses Corporate Social Responsibility in the Meat Industry by analyzing the reflexes of the Sustainable Development Goals (SDGs) and the stakeholder demands in projects of a socio-environmental nature. It is, therefore, an exploratory research and with a qualitative approach. The four food industries that were classified in the Novo Mercado, by Bolsa Brasil Balcão (B3), the São Paulo stock exchange, were analyzed. Content analysis of the documentary stage was performed and, subsequently, also of the answers obtained from the participating managers. It can be concluded that there are several social responsibility actions of these industries in the observed period (2016 to 2020) related to the SDGs, with some of the stakeholders identified by them. Through this research it was possible to see that the SDGs are being partially considered by the companies studied and can be more emphasized, as well as the strengthening of the relationship with stakeholders.